Fruit Fly (Bactrocera spp.) Attack on Tomato Plants (Lycopersicum esculentum Mill.) At Alahan Panjang Vegetable Production Center of Solok Regency, West Sumatera - Zulya Eka Putri; Munzir Busniah; My Syahrawati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2025)
Fruit fly (Bactrocera spp.) is one of the important pests that causes the decline in the quality and quantity of tomatoes in Alahan Panjang, Solok Regency. This study aims to determine the species, population, and rate of fruit fly attacks on tomato plantations in Alahan Panjang. The research uses a survey method and sample determination uses the purposive sampling method. The research locations are in Lembah Gumanti District, Danau District and Lembang Jaya District. The observation parameters are the planting conditions, species, population, and rate of fruit fly infestation. The results of the study revealed that three species of fruit flies attacked tomato plants, namely B. carambolae, B. dorsalis, and B. papayae. The highest imago population was found in Lembah Gumanti District (736 individuals/land), while the lowest number of fruit fly imago was found in Lembang Jaya District (45 individuals/land). The highest percentage of infested tomato plants occurred in Lembah Gumanti District at 72.5% while the lowest percentage of infested plants occurred in Lembang Jaya District at 42.5%. The highest percentage of infected fruits was in ripe fruits in Lembah Gumanti District at 23.07%, while the lowest percentage of infected fruits occurred in unripe fruits in Lembang Jaya District at 10.53%.